Continuity in Sex-Typed Behavior from Preschool to Adolescence: A Longitudinal Population Study of Boys and Girls Aged 3-13 Years. - Golombok, Susan; Rust, John; Zervoulis, Karyofyllis; Golding, Jean; Hines, Melissa (Archives of Sexual Behavior, 2012)
Sex-typed behavior was assessed at age 3 using the Pre-School Activities Inventory, and at age 13 using the Multidimensional Gender Identity Scale, in 54 masculine boys, 57 masculine girls, 75 feminine boys, 65 feminine girls, 61 control boys, and 65 control girls. At age 13, girls who had been masculine at age 3 felt less similar to other girls, were less content being a girl, and had greater self-efficacy for male-typed activities than control girls, and girls who had been feminine at age 3 had greater self-efficacy for female-typed activities. Boys who had been feminine at age 3 felt less similar to other boys and had lower self-efficacy for male-typed activities than control boys at age 13, and boys who had been masculine at age 3 felt more competent in agentic roles. Thus, sex-typed behavior at age 3 predicted sex-typed behavior at age 13. It was concluded that the degree of sex-typed behavior shown by preschool children is a good indicator of their degree of sex-typed behavior following the transition to adolescence.